Microfinance and welfare of households in Ngcobo villages in the Eastern Cape Province - Nkungwana, Sihle Charity (Graduate School of Business (GSB), 2021)
This research examined the effectiveness of microfinance on welfare of rural households in Ngcobo in the Eastern Cape through an administered survey. The study targeted fifty households based on convenience sampling technique and used a number of welfare indicators but selected food consumption patterns; roof, floor and walls of the main dwelling house; cooking fuel used and transport, livestock and household appliances and electronics asset ownership patterns to derive household welfare index. The derived household welfare index of those households which have had microfinance access was then compared with that of those households that have never accessed microfinance. The general idea was that microfinance access would result in relatively higher welfare. The study found microfinance access to have a significantly high impact t highly on household welfare index of those households that had participated in microfinance in Ngcobo. The higher household welfare index meant that microfinance beneficiaries had relatively higher protein consumption patterns, used more durable material for roofs, wall and floors of their main dwellings, had better asset ownership patterns in particular variety of household appliances and electronics. The study also found that there are other control variable such as employment, age, household size and education that interfere with access to microfinance. Lastly, the study also found that that distance of a household from a microfinance outlet or institutions plays a significant hindrance factor in microfinance access. In other words, those households in Mjanyana and Clarkebury, which are situated within more than 40 kilometres from the microfinance institutions, had lower microfinance access. Based on the findings, the study recommends that policy makers in the province pay attention in refining the policy to ensure that control variables identified to interfere with microfinance access do not close out the intended beneficiaries of microfinance. Also, the study recommends that policy makers and microfinance institutions be innovative in ensuring those in deep rural areas are offered the same opportunity to access microfinance within Ngcobo, despite their distance from the microfinance outlets.